2018
DOI: 10.20517/2574-1225.2018.25
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of early rectal cancer in the era of adjuvant and neo-adjuvant therapy

Abstract: The accurate staging of rectal cancer improves the stratification of patients for adjuvant therapy. Staging of tumor with endoluminal ultrasonography (EUS) shows a good correlation with histology (κ = 0.85; 95% confidence interval 0.76-0.95). Overall pT and pN stage accuracy of EUS was 92% and 65% respectively. The staging of local disease can be further augmented by EUS guided fine needle aspiration of extra rectal lesions lying within or outside of the mesorectum. In a systematic review of local excision aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Splenic flexure mobilization was performed in 71.3% (50 women and 72 men) of patients, two of which had anas- tomotic leakage in our study. Most of authors recommend splenic flexure mobilization to decrease the tension in colorectal anastomosis since it will decrease the leakage risk (26). Despite the fact that splenic flexure was mobilized, the incidence of anastomotic leak in most of our cases showed that other factors may be responsible rather than tension.…”
Section: Discussionmentioning
confidence: 63%
“…Splenic flexure mobilization was performed in 71.3% (50 women and 72 men) of patients, two of which had anas- tomotic leakage in our study. Most of authors recommend splenic flexure mobilization to decrease the tension in colorectal anastomosis since it will decrease the leakage risk (26). Despite the fact that splenic flexure was mobilized, the incidence of anastomotic leak in most of our cases showed that other factors may be responsible rather than tension.…”
Section: Discussionmentioning
confidence: 63%